The Effect of Metal-Metal and Metal-Oxide Interactions on Electrocatalytic Activity of Pt Thin Film Catalysts - Tripković, Dušan (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The electrocatalytic oxidation of small organic molecules, such as methanol, ethanol and formic acid has been extensively studied due to their properties that make them suitable for use in fuel cells. Particularly, the electrochemical oxidation of formic acid has been comprehensively examined as the anodic reaction in direct formic acid fuel cell (DFAFC). In this study, we have investigated how the change in surface composition of the Pt thin film deposited on Ni and Cr supports, induced by the controlled thermal treatment, reflects on catalyst performance for the electrooxidation of formic acid. In order to explain the results obtained, the catalysts were characterized using the photoelectron spectroscopy (XPS) to determine the composition of the electrode surface before and after annealing. Electrooxidation of adsorbed carbon monoxide layer and in situ FTIR technique helped us explain the difference in performances recorded in electrooxidation of formic acid. AFM and STM analysis were essential to provide the insight into the alteration of the morphology induced by thermal annealing. Finally, in situ ISPMS analysis was performed to determine the electrode stability during the formic acid oxidation reaction.